ANALISIS PSIKOLOGIS TOKOH UTAMA DALAM CERITA SWARGA ROHANA PARWA - Indah Pramesti, Ni Made Ari (Humanis; Volume 7. No. 2. Mei 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Study of structure and psychology in Swarga Rohana Parwa aim for understanding the elements that built structure and psychology, and also aim for recognizing the connote signs which is need to interpreted in order to get the precise and useful information in Swarga Rohana Parwa. Theoretical used in this study is structure and psychology theory. Structure theory used based on Teeuw; the prominent elements in a literature. For psychology analysis is based on theory declared by Sigmund Freud who analyze the psychology of promainent figure in Swarga Rohana Parwa. Method used in this study consists of three steps i.e. data collecting, data analysis and result presentation. Result of this study shows that there are exist some elements such as Plot, Latar (backround), and Penokohan (character). Plot that is a course of story in Swarga Rohana Parwa. Latar (backround) pervade place, time, and milieu. And last one is Penokohan (character) divisible as three i.e. promainent figure, secondary figure, and complement figure. Psychology of promainent figure pervade i.e. Id (pleasure principle), Ego (reality principle), and Superego. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Parwa, Structure, Psychology. 1. Latar